2015
DOI: 10.1016/j.juro.2015.04.104
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Spontaneous Stone Passage and the Potential Role of Serum C-Reactive Protein in Patients with 4 to 10 mm Distal Ureteral Stones: A Prospective Clinical Study

Abstract: Stone size, previous spontaneous passage, hydronephrosis, serum C-reactive protein and white blood count can be used to predict spontaneous stone passage in patients with 4 to 10 mm distal ureteral stones. A serum C-reactive protein level of 0.506 mg/l can serve as a cutoff value to predict spontaneous stone passage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 21 publications
4
35
2
2
Order By: Relevance
“…C-reactive protein could also be used as a predictor of spontaneous passage of ureter stones. Simple uncomplicated ureter stone patients might have low CRP levels [23,24]. The AUROC of the modified STONE and the sensitivity of the high score were significantly higher than those of the STONE score, which needs further multicenter external validation.…”
Section: Discussionmentioning
confidence: 88%
“…C-reactive protein could also be used as a predictor of spontaneous passage of ureter stones. Simple uncomplicated ureter stone patients might have low CRP levels [23,24]. The AUROC of the modified STONE and the sensitivity of the high score were significantly higher than those of the STONE score, which needs further multicenter external validation.…”
Section: Discussionmentioning
confidence: 88%
“…Studies that used a multivariate analysis of potential predictors of obstruction noted an association between spontaneous stone passage and degree of hydronephrosis, although this association was not present for other secondary signs of obstruction. [11][12][13] Therefore, few studies have examined the impact of calculus-induced UTO independent from individual secondary CT signs in a manner clinically relevant to urologists and emergency physicians.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, most importantly, we found that obstruction was not an independent criterion for intervention, which is inconsistent with previous studies reporting an association between intervention and degree of hydronephrosis. [11][12][13] Taylor et al, for example, recently reported a + likelihood ratio (LR) of 1.45 for mild hydronephrosis and 3.05 for moderate to severe hydronephrosis. 13 One explanation for this apparent inconsistency is that since hydronephrosis may not be present if obstruction is detected early, it may be an indicator of a more severely decompensated collecting system.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of univariate and multivariate analysis performed by Özcan et al, the presence of hydronephrosis was reported as a predictive factor for SP. In a univariate analysis conducted by Zorba et al a significant correlation was detected between SP and the presence of hydronephrosis [9,15]. However, in multivariate analysis the presence of hydronephrosis did not appear to be an independent predictive factor.…”
Section: Discussionmentioning
confidence: 89%
“…To summarize, the authors determined that C-reactive protein (CRP) and white blood cell (WBC) values were correlated with SP. They also stated that when deciding on MET for SP these parametres should be taken into consideration [15,16]. Tchey et al investigated the impact of BMI and the history of SP in addition to the parametres of SP time and stone size suitable for SP.…”
Section: Discussionmentioning
confidence: 99%